The utilization of space and time in primary schools under the Cape Education Department : a critical study of certain aspects - Koker, J. R.(Jan Robert) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ed.) -- Universiteit van Stellenbosch, 1979.